New insights into the interplay between long non‐coding RNAs and RNA‐binding proteins in cancer - Yao, Zi‐Ting; Yang, Yan‐Ming; Sun, Miao‐Miao; He, Yan; Liao, Long; Chen, Kui‐Sheng; Li, Bin (Cancer communications (London, England), 2022)
With the development of proteomics and epigenetics, a large number of RNA‐binding proteins (RBPs) have been discovered in recent years, and the interaction between long non‐coding RNAs (lncRNAs) and RBPs has also received increasing attention. It is extremely important to conduct in‐depth research on the lncRNA‐RBP interaction network, especially in the context of its role in the occurrence and development of cancer. Increasing evidence has demonstrated that lncRNA‐RBP interactions play a vital role in cancer progression; therefore, targeting these interactions could provide new insights for cancer drug discovery. In this review, we discussed how lncRNAs can interact with RBPs to regulate their localization, modification, stability, and activity and discussed the effects of RBPs on the stability, transport, transcription, and localization of lncRNAs. Moreover, we explored the regulation and influence of these interactions on lncRNAs, RBPs, and downstream pathways that are related to cancer development, such as N6‐methyladenosine (m6A) modification of lncRNAs. In addition, we discussed how the lncRNA‐RBP interaction network regulates cancer cell phenotypes, such as proliferation, apoptosis, metastasis, drug resistance, immunity, tumor environment, and metabolism. Furthermore, we summarized the therapeutic strategies that target the lncRNA‐RBP interaction network. Although these treatments are still in the experimental stage and various theories and processes are still being studied, we believe that these strategies may provide new ideas for cancer treatment.